An empirical assessment of students’ perceptions on integrated educational factors in Islamiyyah Madrasah in North-Central Nigeria - Surajudeen, Ahmad Tijani; Awang Mat , Muhamad Zahiri (IIUM Press, 2015)
As a response to the problem of dualism, the First World Conference on Muslim Education (Makkah, 1977) proposed the establishment of integrated education in the Muslim world. There is a gap in the literature regarding the implementation of integrated education in the Nigerian context despite an emphasis on the vitality of integrated education paradigm. This study investigated the perceptions of students about integrated education in the context of Islamiyyah madrasah in North-Central Nigeria. A survey questionnaire was used to collect data from 344 respondents in selected Islamiyyah madrasah in the country. The findings indicate that the majority of the respondents perceived that Islamiyyah madrasah balances between Islamic and Western education. The majority of the respondents agreed that they used dialogical pedagogy which allows students to participate during teaching and learning. Moreover, they believed that Islamiyyah madrasah promotes the integration of technology in teaching and learning. In conclusion, it was recommended that the three components of integrated education should be harmonized in order to foster the personality of the learners. Drastic efforts are required to propel integrated education in order to provide opportunity for learners to compete favorably with students of public schools. This necessitates support from all, stakeholders including, government authorities, the National Board of Arabic and Islamic Studies (NBAIS) among others.